Անձնային գործոնների դերը երիտասարդների ինքնաիրացման գործընթացում - Էբթեսամ Փաժուհանդեհ (ՀՀ ԳԱԱ հրատ.)
In the article the problem of characteristic of person which are influence on the self—realization was discussed. Personal factors coming from person's character submitted in sphere of communication, emotional and intellectual fields. In the process of self- realization the big role have a professional selection and orientation. In the article also given a comperativ analysis between the personal factors among local and non-local student. In Iran the components of self - realization in the new educational environment includes stability developed values, need for knowledge, creativity and self - percapition.
Keywords: Psychology